Highly Efficient Ammonia Synthesis Electrocatalyst: Single Ru Atom on Naturally Nanoporous Carbon Materials. Issue 5 (25th March 2018) - Cao, Yongyong; Gao, Yijing; Zhou, Hu; Chen, Xianlang; Hu, Hui; Deng, Shengwei; Zhong, Xing; Zhuang, Guilin; Wang, Jianguo
Abstract: Stabilizing single‐atom metal catalysts with carbon materials and utilizing their synergistic effect remains challenging due to weak interactions between carbon‐based supports and metals. Density functional theory (DFT) calculations indicate that a single Ru atom was supported on a wide range of natural nanoporous carbon materials, including C2 N, triazine‐C3 N4 (T‐C3 N4 ), and γ‐graphene. These carbon materials belong to a new generation of highly efficient electrocatalysts for the N2 reduction reaction (NRR) and are named Ru1 @C2 N, Ru1 @T‐C3 N4, and Ru1 @γ‐graphyne, respectively. Ab initio molecular dynamic (AIMD) simulations show that a single Ru atom can be stably anchored in the nanopores of these carbon materials with strong cohesive energy. Compared with parallel adsorption configuration, the vertical adsorption configuration of N2 exhibits higher adsorption energy. The calculated Gibbs free energy reveals N2 reduction on the three catalysts via associative mechanisms. Despite the similar limiting potentials (−0.96, −0.94, and −0.98 V on Ru1 @C2 N, Ru1 @T‐C3 N4, and Ru1 @γ‐graphynes, respectively), the limiting step differs, indicating the significant effects of carbon material substrates on electrochemical NRR. However, the competitive and efficient hydrogen evolution reaction (HER) changes the potential determining step and increases the overpotential for the electrochemical nitrogen reduction (NRR). This study provides insights for experimental synthesis of electrocatalysts for N2 reduction. Abstract : The single Ru atom can be strongly anchored in the natural nanopores of carbon materials (C2 N, T‐C3 N4, and γ‐graphynes) . There is a synergistic effect between the single Ru atom and carbon materials. Compared with dissociative mechanisms, the associative mechanisms are dominant for Ru1 @C2 N, Ru1 @T‐C3 N4, and Ru1 @γ‐graphyne. Electrochemical N2 reduction reaction (NRR) has a similar limiting potential on these catalysts.